PERAN WORLD FOOD PROGRAMME (WFP) DALAM MEMBANTU INDONESIA MENANGANI ISU KEAMANAN PANGAN DI PROVINSI NUSA TENGGARA TIMUR PADA TAHUN 2005-2009 - Arthur Yoseph, Agung Christopher; Sushanti, Sukma; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT East Nusa Tenggara is a Food Insecurity Province in Indonesia in 2000-2005 and that’s make that issue is important in that country. World Food Program (WFP) is an International Organization Agency that provides food assistance when the issue of Food Security in Indonesia occurs. WFP collaborates with the Indonesian government to build programs to create appropriate food security conditions in vulnerable areas such as East Nusa Tenggara. WFP plays a full role in its assistance to national and regional governments which the government believes can be a solution to solve these food problems. This study focused on explanation of the role of international organizations such as WFP in helping Indonesia solve food security issues in one of the provinces in Indonesia, namely NTT, and purpose of this study also present a descriptive analysis of roles and functions of international organizations in helping countries face national food security issues. Keywords : World Food Programme, Food Security, Internasional Organization, East Nusa Tenggara